Ethics of antibiotic allergy - Xiang, Yu Yi (Journal of medical ethics, 2024)
Antibiotic allergies are commonly reported among patients, but most do not experience reactions on rechallenge with the same agents. These reported allergies complicate management of infections in patients labelled as having penicillin allergy, including serious infections where penicillin-based antibiotics are the first-line (most effective and least toxic) treatment option. Allergy labels are rarely questioned in clinical practice, with many clinicians opting for inferior second-line antibiotics to avoid a perceived risk of allergy. Reported allergies thereby can have significant impacts on patients and public health, and present major ethical challenges. Antibiotic allergy testing has been described as a strategy to circumvent this dilemma, but it carries limitations that often make it less feasible in patients with acute infections or in community settings that lack access to allergy testing. This article provides an empirically informed ethical analysis of key considerations in this clinical dilemma, using Staphylococcus aureus bacteraemia in patients with penicillin allergies as a case study. We argue that prescribing first-line penicillin-based antibiotics to patients with reported allergies may often present a more favourable ratio of benefits to risks, and may therefore be more ethically appropriate than using second-line drugs. We recommend changes to policy-making, clinical research and medical education, in order to promote more ethically acceptable responses to antibiotic allergies than the status quo.